Transitivity System of Markobar Text In Traditional Angkola Marriage - Agustina Siregar, Elitaria Bestri; Dinamika, Soraya Grabiella; Muhammad Ridwan (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
This research aims to describe transitivity process types in Markobar text. Quantitative data supported this qualitatively-oriented descriptive study. The subject of the investigation is a Markobar text in Angkola language. The research was designed using qualitative content analysis. Six indigenous elders and four parents were purposively selected as participants in this study. The data source used is oral data in the form of transcripts. Transitivity in Halliday's systemic functional grammar theory was applied to the data analysis. The study reveals the following two primary findings: 1) All of the six process types can be found in Angkola Markobar text; 2) Material process and mental process are the most frequently occurred process types in the traditional traditional text of Angkola. The dominant use of material process suggests that brides ought to practice the traditional Angkola skills mentioned. Besides, because Markobar text is a kind of oral tradition, the dominant use of mental processes places emphasis on expressing the innermost feelings, ideas, and views of Angkola people.